Questionnaire Study on the Use of Face Masks during the Covid-19 Pandemic among the Dentists and General Public o f Virajpet Town - Ananya Elchuri; Rashmi S Pattanshetty; Abhiraami ​ Shaji; V V Swathi Priya; Gayathry S Menon; Caroline Shaji (Journal of Multidisciplinary Dental Research)
Masks should be used as part of the comprehensive strategy of measures to suppress transmission of COVID-19 and save lives. The aim of the study was to assess the use of face masks among the dentists and general public in Virajpet town. A survey was conducted by distributing a questionnaire (Google forms) to the subjects after obtaining informed consent. A total of 316 individuals in 18-50 age group were surveyed. Cloth mask was used most commonly (61.1%) followed by N95 masks (49.7%), Surgical three ply masks (41.1%) and Respirator (4.1%).88% of the surveyed population reported hand sanitization measures after wearing face masks. Majority of subjects wore face masks for less than 1 hour duration (upto 38%) in a day. The most common reported side effect was sweating (38.9%) followed by Breathing Difficulty (31.6%), Itching (12.7%) and Slurred Speech (9.5%). The results of our study may be of help in construction of general public education campaigns on the proper use of face masks. Keywords: Pandemic, Coronavirus, Facemasks